Buried alive in the dungeon: Examining the patriarchal language of religion and how acts of faith inform GBV in sacred spaces - Dlamini, Zamantshali (Stellenbosch theological journal, 2023)
The church is still an unsafe terrain that breeds patriarchal ideologies. These ideologies are entrenched through religion and culture, sanctioned within the institution of marriage. In conversation with Denise Ackermann and Mercy Oduyoye's West African Women Theology as a theoretical lens, this article amplifies the voices of African women in the context of the Anglican Church of South Africa (ACSA) on their lived experiences of GBV. This essay seeks to establish the life-denying theologies or acts of faith within ACSA that encourage married women to stay in abusive marriages. Data used in this paper emerged from the semi-structured interviews collected between January 2021 and July 2021 from the Diocese of Natal. Data revealed that teachings on male headship, silence and forgiveness and marriage and divorce play a role in the abuse. Unmasking toxic theologies is fundamental for interventions to be relevant.